PERCERAIAN DAN NASIB ANAK: EVALUASI TERHADAP EFEKTIVITAS PENGAWASAN PELAKSANAAN PUTUSAN HAK ASUH OLEH PENGADILAN DI INDONESIA - Syifa Ramadani; Sidi Ahyar Wiraguna (PT. Hasba Edukasi Mandiri, 2025)
The increasing rate of divorce in Indonesia directly impacts the protection of children's rights, particularly in the determination of custody. This study aims to analyze the application of the best interest of the child principle as well as the effectiveness of children's participation and supervision of custody decisions. Using a juridical-empirical approach with a qualitative method, this study examines religious court decisions and conducts interviews with judges and related parties. The results show that custody determinations are still formalistic, dominated by the rigid application of Article 105 of Law No. 1 of 1974, which automatically grants custody to the mother without a holistic consideration. Children's participation in the court process is almost non-existent, and there is no post-decision supervision mechanism. As a result, many decisions do not substantively reflect the best interests of the child. This study concludes that the family justice system in Indonesia has not fully prioritized children Reforms are needed through technical guidelines, judge training, and an integrated supervision system to ensure the real protection of children's rights after divorce.